Prevalence and risk factors of acne scars in patients with acne vulgaris - Liu, Lin; Xue, Yuzhou; Chen, Yangmei; Chen, Tingqiao; Zhong, Judan; Shao, Xinyi; Chen, Jin (Skin research and technology, 2023)
Background Acne scar is a persistent complication of acne vulgaris. However, the prevalence and risk factors are still unclear. This study aimed to assess the global prevalence and risk factors of acne scars in patients with acne. Materials and methods A systematic search of published studies in three databases was performed and the meta‐analyses were conducted. Results Finally, we included 37 studies involving 24 649 acne patients. And, the pooled prevalence of acne scars in these patients was 47% (95% confidence interval [CI]: 38–56%). Besides, the differences in prevalence were observed based on the subgroup analysis for age, gender, acne severity, source of patients, and so on. Subsequently, we quantified the relationship of three risk factors with acne scars: male gender (odds ratio [OR]: 1.58, 95% CI: 1.19–2.09), positive family history of acne (OR: 2.73, 95% CI: 1.26–5.91), and acne severity (OR for moderate acne: 2.34, 95% CI: 1.54–3.57; OR for severe acne: 5.51, 95% CI: 2.45–12.41). Conclusion Herein, we found that 47% of acne patients suffered from acne scars and identified three risk factors: male gender, positive family history of acne, and acne severity. In order to reduce acne scarring, attention and effective therapy early in the course of acne is important.